Electroretinographic assessment of retinal function at high altitude. - Schatz, A; Willmann, G; Fischer, M; Schommer, K; Messias, A; Zrenner, E; Bartz-Schmidt, K; Gekeler, F (2013)
Although hypoxia plays a key role in the pathophysiology of many common and well studied retinal diseases, little is known about the effects of high-altitude hypoxia on retinal function. The aim of the present study was to assess retinal function during exposure to high-altitude hypoxia using electroretinography (ERG). This work is related to the Tübingen High Altitude Ophthalmology (THAO) study. Electroretinography was performed in 14 subjects in Tübingen, Germany (341 m) and at high altitude at La Capanna Regina Margherita, Italy (4,559 m) using an extended protocol to assess functional integrity of various retinal layers. To place findings in the context of acute mountain sickness, correlations between ERG measurements and oxygen saturation, heart rate, and scores of acute mountain sickness (AMS) were calculated. At high altitude, the maximum response of the scotopic sensitivity function, the implicit times of the a- and b-wave of the combined rod-cone responses, and the implicit times of the photopic negative responses (PhNR) were significantly altered. A-wave slopes and i-waves were significantly decreased at high altitude. The strongest correlation was found for PhNR and O2 saturation (r = 0.68; P < 0.05). Of all tested correlations, only the photopic b-wave implicit time (10 cd·s/m(2)) was significantly correlated with severity of AMS (r = 0.57; P < 0.05). ERG data show that retinal function of inner, outer, and ganglion cell layer is altered at high-altitude hypoxia. Interestingly, the most affected ERG parameters are related to combined rod-cone responses, which indicate that phototransduction and visual processing, especially under conditions of rod-cone interaction, are primarily affected at high altitude.